PENGEMBANGAN MEDIA PEMBELAJARAN IPS SEJARAH MELALUI APLIKASI SWAY BERKONTEN INDIS DI SMP NEGERI 8 MADIUN - Khoirul Huda (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2017)
Education in Indonesia is seen from the perspective of the present field experiencing many multicomplex problems. The role of educators in utilizing learning conditions through the composition of teaching tools has not been powerless. Minimnya in designing models, strategies or media that are not adequate. This condition is often seen in SMP Negeri 8 Madiun. Based on the observations mention First, the teaching model of IPS History is still conventional with the lecture method. Educators have not taken advantage of interesting and interactive media variations leading to saturation. Second, the limitations of resource utilization. Whereas the surrounding environment learning source can be used for learning IPS History such as Indis building (Housing Employee KA, SMPN 1 Madiun School Building, City Hall, Giringan PLTA, pagotan sugar factory and kawedanan Uteran or Kandangan coffee garden). The purpose of this research is to develop the media office Sway berkonten Indis to form a draft prototype that has been tested. Research type is Research and Development. The result of this research is limited test at SMP Negeri 10 Madiun got average score 4,23, produce very good score (X => 4,21) so media is considered feasible. The expanded scale test at SMP Negeri 8 Madiun shows the average of 60,35 (pre-test) and 94,46 (post-test), and statistic test of Paired Samples T Test. The result of significance value is 0.00, so the result shows less than 0.05 and  means rejected so that there has been a significant increase.